2000
DOI: 10.1034/j.1399-6576.2000.440809.x
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous sympathetic vasoconstrictor reflexes for the evaluation of interscalene brachial plexus block

Abstract: Interscalene brachial plexus block reduces regional sympathetic nervous activity, illustrated by increases in skin blood flow, skin temperature and attenuated vasoconstrictor responses to an inspiratory gasp. The inspiratory gasp vasoconstrictive response is a powerful and sensitive indicator for monitoring the sympathetic blockade following interscalene brachial plexus block.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
25
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 18 publications
6
25
0
Order By: Relevance
“…The effect of the local anaesthetic mixture (bupivacaine and/or lidocaine) used in this study on the autonomic nervous system activity during brachial plexus block has also been studied previously using LDF signals (Landsverk et al 2006, Lehtipalo et al 2000, Szili-Torok et al 2002. Landsverk et al (2006) analysed LDF signals from ASA I patients undergoing hand surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of the local anaesthetic mixture (bupivacaine and/or lidocaine) used in this study on the autonomic nervous system activity during brachial plexus block has also been studied previously using LDF signals (Landsverk et al 2006, Lehtipalo et al 2000, Szili-Torok et al 2002. Landsverk et al (2006) analysed LDF signals from ASA I patients undergoing hand surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In this study HRV signals acquired from a group of patients undergoing local anaesthesia (axillary brachial plexus block) have been analysed to see the effect of local anaesthetic drug on the cardiovascular autonomic control. The inhibitory effect of the Brachial plexus block on the sympathetic and the endothelial activity has been demonstrated in previous studies (Landsverk et al 2006, Lehtipalo et al 2000, Szili-Torok et al 2002 by analysing the laser Doppler flowmetry (LDF) signals. Such information regarding the effect of local anaesthesia on autonomic nervous system could be helpful in anaesthetic management.…”
Section: Introductionmentioning
confidence: 99%
“…We have already shown that changes in percutaneous oxygen pressure (tcPO 2 ) may predict the effects of the spinal anaesthesia when combined with oxygen administration [8]. Therefore, in the present study, we studied the changes in tcPO 2 with the hypothesis that the changes in tcPO 2 may differentiate the blocked arm and non-blocked arm after the brachial plexus block.…”
mentioning
confidence: 99%
“…Blood flow may increase by vasodilation after the brachial plexus block, a phenomenon which also has been much studied [2,[4][5][6][7]. Wenger et al [4] showed that an increase of forearm blood flow by skin temperature rise was not different between the brachial plexus block and the control [4].…”
mentioning
confidence: 99%
See 1 more Smart Citation